Fugitive Ecologies: Marronage and Invasive Species in Jamaica - Favini, John (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2023)
This paper seeks to refine scholarly thinking regarding invasive species and decolonial politics in plantation ecologies by following bamboo’s contradictory relationships to various parties on the island of Jamaica. Planters imported bamboo to Jamaica for its remarkable propensity to grow, a quality that soon let it loose on the island’s hinterlands. There, bamboo allied with a people whose flight mirrored its own: Maroons, or fugitive African and Indigenous Taino people who built autonomous communities in the island’s interior. Lately, bamboo is on the move again, precipitating an ecological “invasion” in the eyes of the island’s conservationists and an opportunity for green growth from the perspective of its business interests. These parties, though differing in many ways, both approach bamboo through an idiom of mastery with roots in the plantation and colonial forestry. Maroons, on the other hand, model a creative openness to more-than-human encounters, building relationships to bamboo that are both quotidian and sacred, salutary and trying, but which point toward Maroon autonomy. I offer the concept of fugitive ecologies to attune scholars to these patchy geographies of partial freedom Maroons build with this “invasive” collaborator at the plantation’s edges. Whereas existing paradigms within the environmental humanities tend to focus on species-level classification, fugitive ecologies allow us to see how plants and animals—native, invasive, or otherwise—can “become with” Black freedom struggles.